2005
DOI: 10.1007/s10600-005-0128-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Compositions of Seed Oils of Three Turkish Salvia Species and Biological Activities

Abstract: The fatty acid composition of seed extracts of Salvia bracteata, S. aethiopis, and S. candidissima ssp. candidissima were analyzed by GC/MS. The main compound of S. bracteata, S. aethiopis, and S. candidissima ssp. candissima was found to be 9,12-octadecenoic acid at 64. 3%, 73.4%, and 20.8%, respectively. The seed extracts of S. bracteata showed activity against S. aureus E. coli, M. smegmatis, and C. albicans with MIC values of 1.1, 0.5, 1.1, and 1.1 mg/mL, respectively, while the seeds extract of S. aethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
12
1
Order By: Relevance
“…The seeds extract, rich in fatty acids (such as 9,12-octadecenoic acid accounting for the 64.3%), showed activity against Staphylococcus aureus, Escherichia coli, Mycobacterium smegmatis, and Candida albicans (Kilic et al, 2005). The essential oils of Salvia bracteata collected in Turkey (Ozen et al, 2004), and Iran (Amiri, 2007;Sefidkon et al, 2007), were also studied.…”
Section: Introductionmentioning
confidence: 99%
“…The seeds extract, rich in fatty acids (such as 9,12-octadecenoic acid accounting for the 64.3%), showed activity against Staphylococcus aureus, Escherichia coli, Mycobacterium smegmatis, and Candida albicans (Kilic et al, 2005). The essential oils of Salvia bracteata collected in Turkey (Ozen et al, 2004), and Iran (Amiri, 2007;Sefidkon et al, 2007), were also studied.…”
Section: Introductionmentioning
confidence: 99%
“…Another study determined that the linoleic acid amount of 13 Salvia taxa ranged from 12.8% to 52.2% and that the linolenic acid amount was between 3.2% and 45.2% [20]. The seed oils of 13 of the studied Salvia taxa amounted to 12.1-60.4% for linoleic acid, 2.1-57.6% for linolenic acid, and 11.3-30.7% for oleic acid [6].…”
mentioning
confidence: 97%
“…However, twenty components comprised between 0.1-8.0 %, while twenty-three compounds were present in trace amounts (Table 1). The chemical composition of our oil was found to be closely similar to that of the same species collected in Italy [9], Yugoslavia [11], Bulgaria [17], and Iran [19] which were characterized by its large amount of oxygenated fraction.According to previous data of the chemical composition of the oils obtained by hydrodistillation, steam distillation, or ethanol extraction from aerial parts of S. officinalis from different countries [6,8,9,[11][12][13][14][15][16][17][18][19], α-thujone, α-humulene, and camphor have been reported to be the major compounds in these oils (Table 2).Finally, our results are in agreement with samples of Italian [9], French, Romanian, Czech, Portuguese [13], and Turkish [17] sage oils characterized by camphor (22.0-32.9%) as the most important component, in contrast, samples from many countries are represented by α-thujone (21.5-31.5%) and α-humulene (14.7%) [7] as the major compounds in their oils. However, a comparison of the composition of the Iranian sage oils during the different developmental stages revealed that 1,8-cineole (15.3-22%), α-thujone (9.1-25.1%), and β-pinene (7.1-16.4%) were the principal compounds [19] (see Table 2).…”
mentioning
confidence: 99%
“…According to previous data of the chemical composition of the oils obtained by hydrodistillation, steam distillation, or ethanol extraction from aerial parts of S. officinalis from different countries [6,8,9,[11][12][13][14][15][16][17][18][19], α-thujone, α-humulene, and camphor have been reported to be the major compounds in these oils (Table 2).…”
mentioning
confidence: 99%